2014
DOI: 10.1371/journal.pone.0114507
|View full text |Cite
|
Sign up to set email alerts
|

Annexin-A1 Regulates MicroRNA-26b* and MicroRNA-562 to Directly Target NF-κB and Angiogenesis in Breast Cancer Cells

Abstract: Annexin 1 (ANXA1) is an endogenous anti-inflammatory protein implicated in cancer. ANXA1 was previously shown to be regulated by hsa-miR-196a. However, whether ANXA1 itself regulates microRNA (miR) expression is unknown. Therefore, we investigated the regulation of miR by ANXA1 in MCF7 breast cancer cells. MCF7-EV (Empty vector) and MCF7-V5 (ANXA1-V5 expressing cells) were subjected to a miR microarray. Microarray analysis revealed a number of miRNAs which were dysregulated in MCF7-V5 cells. 2 novel miRNAs (mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 37 publications
3
35
0
Order By: Relevance
“…Consistent with our findings, a recent study has also revealed that upregulated ANXA1 was associated with resistance to various chemotherapeutic agents (10). ANXA1 activates NF-κB, which is known as the association of resistance to 5-FU, resulting in progression of metastasis (12). The investigation of resistance mechanisms to chemotherapies is strongly required to develop anticancer therapies with high efficacy and minimum risk of adverse events.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with our findings, a recent study has also revealed that upregulated ANXA1 was associated with resistance to various chemotherapeutic agents (10). ANXA1 activates NF-κB, which is known as the association of resistance to 5-FU, resulting in progression of metastasis (12). The investigation of resistance mechanisms to chemotherapies is strongly required to develop anticancer therapies with high efficacy and minimum risk of adverse events.…”
Section: Discussionsupporting
confidence: 89%
“…Assuredly, systemic administration of AnxA1 2–26 enhanced the number of new vessels in the transplanted tissue and enhanced local gene and protein expression of VEGF-A, showing a pro-angiogenic action of the peptide. The direct role of AnxA1 on angiogenesis has not been described, as data regarding AnxA1 on angiogenesis were obtained in in vivo and in vitro tumorigenesis conditions, and data suggest that the tumor microenvironment is determinant to angiogenic actions of AnxA1 ( Oh et al, 2004 ; Yi and Schnitzer, 2009 ; Anbalagan et al, 2014 ). Remarkably, our in vivo data showed the ability of AnxA1 2–26 to induce angiogenesis in the subcutaneous tissue, equivalent to that caused by VEGF-A.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA profiling has previously been reported in tumor classification, diagnostics and therapeutics. miR-26b profiling has specifically been reported in angiogenesis in breast cancer cells (24) and epithelial-mesenchymal transi-and epithelial-mesenchymal transition in hepatocellular carcinoma (25). Additionally, miR-26b is downregulated in carcinoma-associated fibroblasts from estrogen receptor-positive breast cancers leading to enhanced cell migration and invasion (26).…”
Section: Discussionmentioning
confidence: 99%